Global and Brazilian Scenario of Guidelines and Legislation on Welfare in Pig Farming - de Castro Lippi, Isabella Cristina [UNESP]; Caldara, Fabiana Ribeiro; de Lima Almeida Paz, Ibiara Correia [UNESP]; Odakura, Agnês Markiy (MDPI, 2022)
The evolution of scientific knowledge regarding animal sentience, together with the growing concerns of consumers regarding current production models, has brought with it the responsibility of reviewing many practices carried out in industrial swine farming, with the purpose of improving the life quality of animals throughout the entire production cycle. In this sense, many initiatives have been taken by European Union, OIE and other countries to abolish questionable practices from an animal welfare point of view, being signed through legislation or normative instructions, which guide governments and companies on the best practices to be adopted. Among the main changes that have taken place in swine farming are the ban or reduction in the use of cages for sows, restrictions on the age at weaning, ban on painful procedures such as surgical castration, tail and teeth clipping, as routine procedures or without the use of anesthesia/analgesia. In addition, these acts also prescribe practices that must be adopted in order to respect the natural behavior of animals, such as the use of environmental enrichment. This review aims to address the main advances made over the last few years in the protection of swine, as well as Brazilian initiatives in this regard.
Keywords: animal welfare; ethics; laws; sentience